2017
DOI: 10.1007/s11948-017-9939-6
|View full text |Cite|
|
Sign up to set email alerts
|

World Map of Scientific Misconduct

Abstract: A comparative world map of scientific misconduct reveals that countries with the most rapid growth in scientific publications also have the highest retraction rate. To avoid polluting the scientific record further, these nations must urgently commit to enforcing research integrity among their academic communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 6 publications
0
10
0
2
Order By: Relevance
“…13,14 Numbers of retracted papers are highest from countries which produce the most publications, namely, the United States and China. 15,16 As research falsification and fabrication are widely recognised to be incorrect practices, they are usually actively concealed by perpetrators and can be difficult to detect. 17 Research fraud is generally considered to be perpetrated by lone actors or teams and to be either driven by factors specific to the researchers themselves (eg, psychiatric illness or outlying research beliefs) or by how rare individuals respond to their research environments.…”
Section: Research Fraud and The Selection Of Unproductive Biomarker Cmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Numbers of retracted papers are highest from countries which produce the most publications, namely, the United States and China. 15,16 As research falsification and fabrication are widely recognised to be incorrect practices, they are usually actively concealed by perpetrators and can be difficult to detect. 17 Research fraud is generally considered to be perpetrated by lone actors or teams and to be either driven by factors specific to the researchers themselves (eg, psychiatric illness or outlying research beliefs) or by how rare individuals respond to their research environments.…”
Section: Research Fraud and The Selection Of Unproductive Biomarker Cmentioning
confidence: 99%
“…13,14 Numbers of retracted papers are highest from countries which produce the most publications, namely, the United States and China. 15,16…”
Section: Introductionmentioning
confidence: 99%
“…Uticaj specifičnih kulturoloških faktora na pojavu nepoštenja u nauci, mogu varirati od društva do društva. U nedavno publikovanoj studiji [25], pokazalo se da zemlje sa najbržim rastom naučnih publikacija imaju najveću stopu retrakcija radova.…”
Section: Diskusija I Zaključakunclassified
“…A multinational retrospective study on previously retracted studies in 2013 showed that Iran, India, and Turkey exhibited higher ratios of publication misconduct to distrusted data (and unreliable interpretations), while the USA, Switzerland, and Germany had higher distrusted data compared to the publication misconduct occasions in the retracted studies (15). Another retrospective study showed that countries with the most rapid growth in scienti c publications (e.g., China, Malaysia, and Mexico) simultaneously exhibited the highest retraction rates (16,17).…”
mentioning
confidence: 99%